(Re)configuring of university extension in the face of COVID-19: the contribution of a postgraduate program (Research, Society and Development, 2022)
The COVID-19 pandemic has caused numerous social, health and educational problems. Social media began to contain an excessive amount of information about the new coronavirus, making it difficult for people to find material from reliable sources. Therefore, a space was created to build knowledge and clarify doubts about SARS-CoV-2 and COVID-19, in addition to developing discussions on educational, technological tools and scientific advances in the search for clarifications and solutions for the confrontation of the current pandemic. The actions were carried out in the virtual space of Instagram, using the lives features, which were broadcast on the @morfotecnologiaufpe profile and took place on Wednesdays at 20 pm and lasting 60 min. The discussions were conducted by mediators, professors from the PPGM-UFPE, and one or two invited experts on each topic addressed. Viewers were able to follow the mediator-guest interaction in real time, in addition to being protagonists of the dialogue through comments and questions. The discussions developed stimulated critical thinking, combating misinformation and valuing science and technology in dealing with health problems. It also corroborates the reorganization of extensionist practices, which are of paramount importance to guarantee the articulation between the university and the community, in the construction of knowledge and in the academic improvement of students and professors. The experience highlighted that the use of social media is an effective tool in health education actions, as it enables accessibility to knowledge through the resources of an Information Technology Platform.